2012
DOI: 10.1007/s00784-012-0703-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological evaluation of high intensity diode laser adjutant to non-surgical periodontal treatment: a 6-month clinical trial

Abstract: The high intensity diode laser did not provide additional benefits to non-surgical periodontal treatment. More studies are necessary to prove the actual need of this type of laser in the periodontal clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 45 publications
7
72
0
1
Order By: Relevance
“…However, there was no statistically significant difference regarding CAL gain between the groups 3 months after treatment in this study. Similarly, some studies have shown no significant difference in attachment gain between cases treated with SRP combined with diode laser 35,36 or PDT 27,37 and those treated only with SRP. These finding are not in agreement with those of some recent randomized clinical trials, which showed that treatment with low-level laser irradiation 38 and PDT 32,39 as an adjunct to conventional SRP have more efficacy in attachment gain than SRP alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no statistically significant difference regarding CAL gain between the groups 3 months after treatment in this study. Similarly, some studies have shown no significant difference in attachment gain between cases treated with SRP combined with diode laser 35,36 or PDT 27,37 and those treated only with SRP. These finding are not in agreement with those of some recent randomized clinical trials, which showed that treatment with low-level laser irradiation 38 and PDT 32,39 as an adjunct to conventional SRP have more efficacy in attachment gain than SRP alone.…”
Section: Discussionmentioning
confidence: 99%
“…So in order to set these parameters that demonstrated that high intensity DL (1.4 W/30 s) did not cause any signs of thermal effects such as charring, necrosis or fusion on the root which inferred about the angle of Laser beam, time and power irradiation on gingival fibroblasts. Other characteristics about this Laser were taken into account in order to use in dental practice: it is one of the cheaper high intensity Laser; furthermore DL machine used in this research is small and light, therefore portable Lasers, as a group, have inconsistently demonstrated the ability to reduce microorganisms within a periodontal pocket [13][14] . Nonsurgical mechanical therapy alone may not effectively eliminate the periodontal disease completely, particularly in deep pockets.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, surgical therapy performed in cases with persistent inflammation, deeper pockets, class II and III bifurcation defects, and intra-bony defects provides better accessibility to root surfaces as well as osseous defects. However, peri-pathogens persist in the mixed-species plaque biofilm on tooth surfaces, adhere to and enter the epithelial cells, and are tissue invasive in nature [13] . These are sources for re-colonization and reinfection.…”
Section: Introductionmentioning
confidence: 99%
“…It leads to thermo coagulation of blood vessels, responsible for its haemostatic effect [26] . DLs are very effective for soft tissue applications including incision, haemostasis and coagulation [27] . Its advantages, include a bloodless operating field, minimal swelling and scarring, and much less or no postsurgical pain.…”
Section: IIImentioning
confidence: 99%